Green nanotechnology : solutions for sustainability and energy in the built environment - Smith, Geoffrey B. (Geoffrey Beaton); Granqvist, Claes G. (Boca Raton, FL : CRC Press, 2011)
This book explores the science and technology of tiny structures that have a huge potential to improve quality of life while simultaneously achieving reductions in the use of fossil fuels. It examines energy flows in nature and how the optical properties of materials can be designed to harmonize with those flows. It then discusses the properties that can be achieved in real materials to take advantage of nature's energy flows.
Green nanotechnology: introduction and invitation -- In harmony with the environment: nature's energy flows and desired materials properties -- Optical materials science for green nanotechnology: the basics -- Visual indoors-outdoors contact and daylighting: windows -- Electric lighting and daylighting: luminaries -- Heat and electricity: solar collectors and solar cells -- Coolness: high-albedo surfaces and sky cooling devices -- Supporting nanotechnologies: air sensing and cleaning, thermal insulation, and electrical storage -- Conclusions: nanotechnologies for a sustainable future.
Includes bibliographical references and index.
Keywords: Sustainable buildings -- Design and construction; Nanotechnology; Buildings -- Electric equipment; Buildings -- Energy conservation; Sustainable construction; Electronic apparatus and appliances